Pengakuan Transaksi Elektronik (E-Commerce) dalam Kerangka Hukum Perikatan dan Kerangka Hukum Pembuktian - Angga Riandra Siregar; Guna Yanti Kemala Sari Siregar Pahu (KEADILAN PROGRESIF, 2017)
E-commerce can be understood as an activity of trade transactions both goods and services through electronic media that provides convenience in the activities of consumer transactions on the internet. So in this context also the inherent legal aspects of the e-commerce mechanism is to interact with the Internet network applications used by parties who make transactions through the e-commerce system.The Consumer Protection Act (UUPK) and the Electronic Information and Transaction Act (UUITE) have been able to provide adequate legal protection for consumers in conducting transactions through e-commerce.In the engagement there is a commitment to do something and not to do anything. What is meant by the engagement to do something is to act in a positive, lawful manner, not violating the law and in accordance with the agreement. While the engagement to not do something that is not to do certain actions that have been agreed in the agreement. Furthermore, the evidence through the law of proof includes several dimensions, such as: the mention of evidences that can be used by the judge to obtain a picture of past events, evidence.